Educational practices with Educational Technologies in basic education: programming, robotic toys, and creative processes (Olhar de Professor, 2025)
This article seeks to discuss Educational Technologies, programming, and robotics in relation to pedagogical practices in basic education. By using Freirean limit-situations and generative themes as methodology, the discussion unfolds through three interrelated scenes that argue how technologies, understood as frameworks (Feenberg, 2003), shape and guide pedagogical practice. It questions how the integration of these technologies can occur through critical dialogue with educators and the school community, in order to prevent these tools from becoming a burden for teachers and reducing pedagogical practice to the mere execution of pre-packaged lessons. The article concludes that Educational Technologies are intertwined with pedagogical practices, transforming them. Even though there is a tendency for them to function as closed methodologies, with little connection to students' realities and needs, it is possible to create custom frameworks to move beyond merely carrying out pre-formatted lessons.
Keywords: Critical education; Teacher autonomy; Hacker culture; Basic education